Association of Serum Homocysteine Level with Migraine in Adults - Islam, Md Monirul; Habib, Md Ahsan; Islam, Md Rafiqul; Rahman, Hasan Zahirur; Rizvi, Abu Nasir; Khan, Rezaul Karim; Bhuiyan, Md Moniruzzaman; Ahtesam, Mohammad Saifullah; Islam, Mohammad Fakrul; Salehin, Mushfequl; et al. (Bangladesh Journal of Neuroscience, 2017)
Background: Migraine is the second most common primary headache disorder that has close link to the neurovascular system. The exact pathogenesis of migraine is still not fully understood but several possible theories have been proposed. Hyperhomocysteinemia is one of the coincidental factors whose association with migraine is yet in obscure. Methods: This case control study was conducted in the department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka. A total of 65 patients, who were diagnosed as migraine (with aura or without aura) according to ICHD-3 criteria, were considered as case group and another 65 patients (age and sex matched) with headache other than migraine were considered as control group. Serum homocysteine levels were estimated for both groups and other relevant investigations were done in selective cases. Comparison of serum homocysteine levels between two groups were done to see association of serum homocysteine level with migraine in adults. Results: A total of 50 women and 15 men with mean age of 31 (±10.41) years and 50 women and 15 men with mean age of 33 (±10.91) years constituted case and control groups, respectively. The mean (±SD) serum homocysteine level in case group 10.71 (±4.16) ìmol/L was significantly higher than control group 7.62 (±2.26) ìmol/L, (P <0.001).The mean value of serum homocysteine level in migraine without aura (MWOA) patients 11.87 (±4.18) ìmol/L was found significantly higher than migraine with aura (MWA) patients 8.23 (±1.51) ìmol/L, (p<0.05). There was no significant correlation between severity of migraine headache and frequency of migraine attack with serum homocysteine level. Conclusion: Serum homocysteine level was found significantly higher in migraineurs than non-migraineurs. Bangladesh Journal of Neuroscience 2017; Vol. 33 (2): 76-82